Pengolahan Hemacookies Dalam Upaya Mencegah Anemia Pada Siswa di SMAN 1 Mlati - Reza Iqbal Suhada; Nurpuji Mumpuni; Rizqi Wahyu Hidayati; Tika Sari Dewi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Anemia is a medical condition characterized by hemoglobin (Hb) levels in the blood below normal, resulting in decreased ability of the blood to carry oxygen to body tissues. Adolescents, especially young women, are a group at high risk of experiencing anemia because the need for iron increases during growth and due to blood loss during menstruation. The prevalence of anemia among adolescents in Indonesia is still high and requires local food-based nutritional interventions for prevention. Hemacookies are designed as a snack with high iron content sourced from green spinach which can help meet adolescents' daily Fe needs. This Community Service aims to develop hemacookies as a functional food product to increase Fe intake and prevent anemia in adolescents at SMAN 1 Mlati. Respondents consumed hemacookies and then their hemoglobin levels were measured. The type of analysis used was descriptive analytic with random sample selection. The results of the community service were 34 respondents. Most of the respondents were female (30 respondents (88.24%) and had normal hemoglobin levels (23 respondents (67.65%). The average hemoglobin level of respondents was 12.81 gr / dl in the normal category. So it can be concluded that hemacookies can prevent anemia in a person.